Prevalence and work‐relatedness of carpal tunnel syndrome in the working population, United States, 2010 national health interview survey1. Issue 6 (11th April 2012) - Luckhaupt, Sara E.; Dahlhamer, James M.; Ward, Brian W.; Sweeney, Marie H.; Sestito, John P.; Calvert, Geoffrey M.
Abstract Background Patterns of prevalence and work‐relatedness of carpal tunnel syndrome (CTS) among workers offer clues about risk factors and targets for prevention. Methods Data from an occupational health supplement to the 2010 National Health Interview Survey were used to estimate the prevalence of self‐reported clinician‐diagnosed CTS overall and by demographic characteristics. The proportion of these cases self‐reported to have been attributed to work by clinicians was also examined overall and by demographic characteristics. In addition, the distribution of industry and occupation (I&O) categories to which work‐related cases of CTS were attributed was compared to the distribution of I&O categories of employment among current/recent workers. Results Data were available for 27, 157 adults, including 17, 524 current/recent workers. The overall lifetime prevalence of clinician‐diagnosed CTS among current/recent workers was 6.7%. The 12‐month prevalence was 3.1%, representing approximately 4.8 million workers with current CTS; 67.1% of these cases were attributed to work by clinicians, with overrepresentation of certain I&O categories. Conclusions CTS affected almost 5 million U.S. workers in 2010, with prevalence varying by demographic characteristics and I&O. Am. J. Ind. Med. 56:615–624, 2013. © 2012 Wiley Periodicals, Inc.